Room-temperature fracture toughness of MoSiBTiC alloys. (May 2017) - Moriyama, Takahiro; Yoshimi, Kyosuke; Zhao, Mi; Masnou, Tiffany; Yokoyama, Tomohiro; Nakamura, Junya; Katsui, Hirokazu; Goto, Takashi
Abstract: Room-temperature fracture toughnesses of TiC-added Mo-Si-B alloys were evaluated for samples of three different compositions prepared using a conventional Ar arc-melting technique. The first alloy (TiCp) had a primary phase during solidification of NaCl-type TiC including an amount of Mo, with a Mo solid solution (Moss ) volume fraction of approximately 49% and a TiC volume fraction of approximately 19%, while the volume fraction of Mo5 SiB2 (T2 ) was approximately 31% and the remaining 1% was Mo2 C including an amount of Ti. The second alloy (T2p) had a primary phase of T2, with volume fractions of Moss, TiC, Mo5 SiB2 (T2 ), and Mo2 C of approximately 38%, 4%, 45%, and 13%, respectively. The third alloy (Mop) had a primary phase of Moss, with volume fractions of Moss, TiC, Mo5 SiB2 (T2 ), and Mo2 C of approximately 55%, 8%, 32%, and 6%, respectively. Room-temperature fracture toughness was evaluated by three different bending tests using Chevron-notched specimens. Fracture toughness values obtained by the three methods were relatively close with good reproducibility. Consequently, the fracture toughness values of TiCp, T2p, and Mop were evaluated to be ∼15.2 MPa(m) 1/2, ∼10.5 MPa(m) 1/2, and ∼13.6 MPa(m) 1/2, respectively. Fracture surface observations indicated that the Moss phase is subject to severe plastic deformation during the fracture process. The TiC phase was also noted to leave river patterns behind through crack propagation. These fractographic results suggest that not only the ductile-phase toughening by the Moss phase but also an extra-toughening mechanism by the TiC phase are responsible for the goodness of the room-temperature fracture toughness of the MoSiBTiC alloys. Highlights: Room-temperature fracture toughness of TiC-added Mo-Si-B alloys is evaluated by three different bending tests. The MoSiBTiC alloy with the primary phase of TiC during solidification has a fracture toughness value better than 15 MPa(m) 1/2 . The fracture toughness values of the MoSiBTiC alloys are in the value range of commercial cemented carbides. TiC phase works to toughen the MoSiBTiC alloys as well as Mo solid solution.